Sentinel node detection in cervical cancer with Tc-99m-phytate - Silva, L. B.; Silva, A. L.; Traiman, Paulo [UNESP]; Triginelli, S. A.; de Lima, C. F.; Siqueira, C. F.; Barroso, A.; Rossi, TMFF; Pedrosa, M. S.; Miranda, D.; Melo, JRC (Elsevier B.V., 2005)
Objectives. The aim of this study was to investigate the feasibility of sentinel lymph node (SLN) identification using radioisotopic lymphatic mapping with technetium-99 m-labeled phytate in patients undergoing radical hysterectomy with pelvic lymphadenectomy for treatment of early cervical cancer.Methods. Between July 2001 and February 2003, 56 patients with cervical cancer 1160 stage I (it 53) or stage 11 (it 3) underwent sentinel lymph node detection with preoperative lymphoscintigraphy (Te-99m-labeled phytate injected into the uterine cervix, at 3, 6, 9, and 12 o'clock, at a dose of 55-74 MBq in a volume of 0.8 ml) and intratoperative lymphatic mapping with a handheld gamma probe, Radical hysterectomy was aborted in three cases because parametrial invasion was found intraoperatively and we performed only sentinel node resection. The remaining 53 patients underwent radical hysterectomy with complete pelvic lymphadenectomy, Sentinel nodes were detected using a handheld gamma-probe and removed for pathological assessment during the abdominal radical hysterectomy and pelvic lymphadenectomy.Results. One or more sentinel nodes were detected in 52 out of 56 eligible patients (92.8%). A total of 120 SLNs were detected by lymphoscintigraphy (mean 2.27 nodes per patient) and intraoperatively by gamma probe, Forty-four percent of SLNs were found in the external iliac area, 39% in the obturator region, 8.3% in interiliae region, and 6.7),) in the common iliac area. Unilateral sentinel nodes were found in thirty-one patients (59%). The remaining 21 patients (4100 had bilateral sentinel nodes, Microscopic nodal metastases were confirmed in 17 (32%) cases. In 10 of these patients, only SLNs had metastases. The 98 sentinel node.,, that were negative on hematoxylin and eosin were submitted to cytokeratin immunohistochemical analysis. Five (5.1%) micrometastases were identified with this technique. The sensitivity of the sentinel node was 82.3% (CI 95% - 56.6-96.2) and the negative predictive value was 92.1% (CI 95% 78.6 98.3) the accuracy of sentinel node in predicting the lymph node status was 94.2%,Conclusion. Preoperative lymphoscintigraphy and intraoperative lymphatic mapping with Tc-99-labeled phytate are effective in identifying sentinel nodes in patients undergoing radical hysterectomy and to select women in whom lymph node dissection call be avoided. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: cervical cancer sentinel lymph node; gamma probe; Tc-99m-fitato; lymphoscintigraphy; lymphatic mapping